Real Estate Investment Trusts in the Developed Countries - Y. A. Burkova (Vestnik MGIMO-Universiteta)
In this article, performance of239 real estate investment trusts (REITs) from 15 developed countries is analyzed according to their regional specific characteristics. This investment vehicle is rapidly spreading all over the world due to high returns it offers while being of low risk, and since the governments create special legislation. In 2013, there were around 30 countries where REITs can be created, so regional specifics of REITs' performance can be studied. USA has the oldest REITs market in the world with 133 trusts operating there. Popularity of American REITs is explained by the fact that they usually hold well diversified portfolios of property with stable income. This helped them rather successfully survive through the global economic crisis of2008-2010, but after that attracted close attention of institutional investors which has led to the creation of new bubble on the market. European REITs market has appeared recently, its development being slowed down by the recent crisis. The debt crisis and liquidity strain caused REITs lack of funds; economic downturn led to the reduction of trusts' returns, resulting in the outflow of the investment to the USA. In 2012, the recovery of the debt capital market reanimated the REITs market. REITs in the Asia-Pacific region are very risky thus offering a high riskpremium. Their returns are unstable and fluctuate in line with the global economic situation. After the crisis, REITs have been the most attractive investment vehicle on the market offering high yield.